2018
DOI: 10.5897/ajmr2018.8887
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of endophytic fungus, Penicillium griseofulvum MPR1 isolated from medicinal plant, Mentha pulegium L.

Abstract: In the present study, an endophytic fungus with a considerable antimicrobial activity was isolated from the medicinal plant Mentha Pulegium L. The morphological and molecular identification revealed that this fungus is a Penicillium griseofulvum. A preliminary screening was done to choose the suitable culture medium for a maximum production of the bioactive compounds using the dual-culture agar diffusion assay. The malt extract agar (MEA) and potato dextrose agar (PDA) media were the suitable, and the MEA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
2
0
1
Order By: Relevance
“…Meanwhile, current findings revealed that ethyl acetate extract was the best organic solvent in extracting bioactive compounds with antibacterial activity due to higher inhibitory d a b c activity than other solvents. A similar observation was reported by Zerroug [30] who claimed that the ethyl acetate was the best solvent used for the extraction of bioactive secondary metabolites from an endophytic fungus, Penicillium griseofulvum MPR1. This phenomenon might be due to its efficiency in extracting and isolating secondary metabolites of fungal origin [31].…”
Section: Discussionsupporting
confidence: 82%
“…Meanwhile, current findings revealed that ethyl acetate extract was the best organic solvent in extracting bioactive compounds with antibacterial activity due to higher inhibitory d a b c activity than other solvents. A similar observation was reported by Zerroug [30] who claimed that the ethyl acetate was the best solvent used for the extraction of bioactive secondary metabolites from an endophytic fungus, Penicillium griseofulvum MPR1. This phenomenon might be due to its efficiency in extracting and isolating secondary metabolites of fungal origin [31].…”
Section: Discussionsupporting
confidence: 82%
“…An endophytic fungus identified as Penicillium griseofulvum , which shows considerable antimicrobial activity, has been isolated from Mentha pulegium Extracts using ethyl acetate ( 119 ) and dichloromethane ( 120 ) show antimicrobial and anticancer activity ( Amina et al, 2018 ). In one study, Arthrinium sp.…”
Section: Polyketidesmentioning
confidence: 99%
“…High activities have been reported for EtOAc ( 119 ) and CHCl 2 ( 120 ) crude extracts of Penicillium griseofulvum MPR1 against E . coli with maximal inhibition zones of 45.5 and 41.0 mm, respectively ( Amina et al, 2018 ). The ethyl acetate extract of Arthrinium sp.…”
Section: Activities Of Metabolites Produced By Endophytic Fungi From ...mentioning
confidence: 99%
“…Os resultados do presente estudo evidenciam que as espécies de Penicillium oriundas da Amazônia sintetizam amilases e proteases, hidrolases utilizadas em diferentes setores industriais, tais como, alimentício e farmacêutico, além de terem ampla aplicabilidade no beneficiamento do couro, papel e celulose (ALVES et al, 2014). A produção de antimicrobianos por Penicillium é influenciada por diversos parâmetros como tipo de bioprocesso, temperatura e a espécie (BARREIRO; MARTÍN; GARCIA-ESTRADA, 2012;ZERROUG et al, 2018). De acordo com Talukdar et al (2016), a síntese de compostos bioativos por espécies de Penicillium com ação inibitória contra microrganismos também é influenciada pela composição do meio de cultivo, com destaque para as fontes de carbono, nitrogênio e minerais.…”
Section: Autenticação Das Espécies De Penicilliumunclassified